From Patrilineal Tradition to Gender Equity: The Evolution of Inheritance Law in Indonesia’s Batak Toba Community - Silalahi, Dwi Grace Rosalia; Lagat Parroha Patar Siadari; Fadlan; Erniyanti; Soerya Respationo (Enigma Institute, 2024)
The Batak Toba community in Indonesia, traditionally governed by a patrilineal kinship system, has historically excluded women from inheritance rights. This deeply ingrained custom has perpetuated gender inequality within the community. However, the landscape of inheritance law has undergone significant transformation due to the influence of national legislation and landmark court rulings. This study explores the dynamic evolution of inheritance practices among the Batak Toba, tracing the shift from a patriarchal tradition to a more equitable system that recognizes the rights of women. This research employs a qualitative approach, combining legal analysis with empirical data gathered through interviews and case studies within the Batak Toba community. The study examines customary laws, national legislation, and judicial decisions to understand the legal framework governing inheritance. Additionally, it delves into the lived experiences of individuals within the community to capture the social and cultural dimensions of inheritance practices. The findings reveal a gradual but significant shift in inheritance practices among the Batak Toba. While the patrilineal tradition remains influential, there is growing recognition of women's inheritance rights. This change is attributed to several factors, including increased education, economic empowerment of women, and greater awareness of gender equality principles. The study also highlights the role of legal reforms and judicial activism in challenging discriminatory customary laws and promoting a more inclusive approach to inheritance. The evolution of inheritance law in the Batak Toba community reflects a broader societal transformation towards gender equity. While challenges persist, the study underscores the importance of continued legal reforms, community engagement, and education to ensure the full realization of women's inheritance rights. The findings offer valuable insights for policymakers, legal practitioners, and community leaders working towards a more just and equitable society.